Nigeria-Rwanda Relations:: Strengthening Partnership for Development - Oluwashakin, Ajinde (Journal of Contemporary International Relations and Diplomacy, 2023)
Nigeria and Rwanda have long existed as colonial states of European imperialism in the 1800s, and gained their independence in the early 1960s, but they never had diplomatic relations until about mid-2000s. In 2011, the Republic of Rwanda opened its High Commission in Abuja, while the FederalRepublic of Nigeria also opened its High Commission in Kigali in 2012. Since the official opening of their diplomatic missions, both countries have been enjoying very cordial bilateral relations in many sectors, especially in socioeconomic ties. It is a relation that has been described by some pundits as, “A big brother, little brother affair”. From this perspective, the paper examines how “big” and “little” brotherly affair can be taken as “equal partnership” to advance economic development for the benefit of both parties. Data were generated from both primary and secondary sources. Primary data was derived from Nigeria High Commission diplomats in Kigali; while secondary data were gathered from newspapers, books and websites. The neoliberal theoretical perspective is adopted as a “partial” approach to analyze the value and volume of economic cooperation and interdependence of state relations. The study revealed that both countries have “signed general agreements for cooperation” which include Air transport agreement between Kigali and Lagos and the Artemis Accord, in Space exploration. As such, the paper stressed the imperative of strengthening of equal partnership that will deliver benefits for both countries’ burgeoning economies. The volume of trade can be increased to boost both countries’ economic development in particular, and Africa’s development in general.